Perancangan Sistem Informasi Penjualan Pada Toko Ribo Jaya Ambon - D. B. Paillin (Industrial Engineering Study Program, Pattimura University, 2012)
Advance in technology, especially computer information technology, encouraging the emergence of new innovations in the presentation of information to meet information needs. As a tool, the computer also has advantages, including speed, accuracy, and efficiency in data processing when compared with manual processing. The computer also penetrated the world of trade and creating fierce competition among merchants. Similarly, Jaya Ribo store which is a trading business buying and selling clothes, being able to provide precise and accurate information in conducting transactions. System running in the store Ribo Jaya is still done manually recording transactions such as purchases, sales transaction records, the search for the goods, the calculation of stock, and making reports which require considerable time and risk of human error is quite great. Based on the research and testing program carried out, there efficiency / reduction in time 63% of the overall average of 10 kinds of stuff manually where it takes 22:27 minutes using a 8:09-minute program and reduce the error rate because the calculations have been done automatically by the program . From the overall results of the study, for saving time and operational costs should trade business form Ribo Jaya using store sales information systems program in the sales transaction.